The Positive Impact of Delegation in Nursing: A Literature Review - Putri, Prestasianita; Tri Afandi, Alfid (D'Nursing and Health Journal (DNHJ), 2023)
Introduction: Good communication with a leader is needed in the delegation process. It is necessary to review the positive impact of delegation. This is expected so that nurses can implement delegation optimally by knowing the positive effects of delegation so that they can carry out good nursing duties and avoid overlapping assignments and late handling. Method: Searching from textbooks, ebooks, and journals, as well as research (original research) related to the positive impact of delegation. Results: Based on the literature review that has been carried out, it can be concluded that the positive impact of delegation in nursing can later be an opportunity for nurses to learn a lot about leadership skills and clarify the strengths and abilities of nurses to use these talents to improve management skills. Conclusion: Based on the literature review that has been carried out, it can be concluded that there are many positive effects of delegation in nursing that can be obtained, and later it can be an opportunity for nurses to learn a lot about leadership skills, clarify the strengths and abilities of nurses to use these talents to improve management skills.